THE RELATIONSHIP BETWEEN MOTIVATION AND THE ENVIRONMENT WITH MALARIA PREVENTION EFFORTS IN THE WORKING AREA OF PUSKESMAS, TENGAH Ilir DISTRICT, TEBO DISTRICT - Alpari Nopindra; Solihin Sayuti; Puspita Sari (International Journal of Medicine and Health, 2022)
Malaria is still a public health problem in Indonesia because of its high morbidity and mortality rates, especially in areas outside Java and Bali. In transmigration areas where there is a mixture of people from endemic and non-endemic areas of malaria, cases or epidemics still frequently occur which cause many deaths. Data from the Tebo District Health Office for January-July 2014 were 519 people out of a population of 328,564 people (0.16%) with an AMI of 1.6. The highest incidence of malaria was in the Mengupeh Health Center, Tengah Ilir District, with 75 people out of a population of 11,820 people (0.63%) with an AMI of 6.34. The purpose of this study was to find out the description and relationship between malaria prevention efforts in the Working Area of ​​the Mengupeh Health Center, Tengah Ilir District, Tebo Regency in 2015. This research is a quantitative study with a cross sectional research design. In this study, the sample was the community in the Working Area of ​​the Mengupeh Health Center, Tengah Ilir District, Tebo Regency, with a sample size of 96 people. The results showed that of the 96 respondents, 57 (59.4%) respondents had poor motivation, 59 (61.5%) respondents had a bad environment, respondents had poor malaria prevention efforts. The results of the analysis showed that there was a relationship between motivation and a p value of 0.007 (p <0.05), environment with a p value of 0.009 (p <0.05) on malaria prevention efforts in the Working Area of ​​the Mengupeh Health Center, Tengah Ilir District, Tebo Regency. Advises the public to be active in seeking information about prevention of malaria in order to reduce the incidence of malaria. At the same time actively maintaining the cleanliness of the home environment and their respective settlements.